Excess DHA Induces Cell Cycle Arrest by Activating the P53/Cycling Pathway in Blunt Snout Bream (Megalobrama amblycephala) - Wang, Cong-cong; Liu, Wen-bin; Cao, Xiu-fei; Huang, Yang-yang; Wang, Xi; Xiao, Kang; Li, Xiang-fei; Zhang, Ding-dong; Jiang, Guang-zhen (Frontiers in Marine Science, 2020)
Pervious study showed that diets with high levels of docosahexaenoic acid (DHA) cause growth retardation in Megalobrama amblycephala. In order to explore the mechanisms, a feeding trial and a primary hepatocyte culture experiment were designed. In vivo, fish (average weight 26.40±0.11 g) were randomly divided into groups and fed three levels of DHA (0%, 0.2% and 1.6% diets, respectively.) for 8 weeks. The results showed that the final body weight and weight gain of fish fed 1.6% DHA were significantly lower than that of fish fed 0.2% DHA (P < 0.05). P53 gene and protein expression levels were significantly increased (P < 0.05), while expression of downstream Cyclin D1 and Cyclin E1 was significantly inhibited in the 1.6% DHA group when compared with the 0% DHA and 0.2% DHA groups (P < 0.05). In vitro, primary hepatocytes isolated from Megalobrama amblycephala incubated with 500 μM DHA showed significantly increased cell cycle arrest and apoptosis (P < 0.05), significantly increased P53 gene and protein levels (P < 0.05), and significantly decreased Cyclin D1 and Cyclin E1 levels (P < 0.05), when compared with other groups. When primary hepatocytes were incubated with DHA and a P53 inhibitor (pifithrin-α), P53 expression and P53-mediated signaling were inhibited, cell cycle progression recovered and apoptosis was reduced. In summary, high levels of DHA activated the P53/Cyclin pathway to induce cell cycle arrest. Inhibition of P53 activity may be a potential way of reducing the side effects of DHA on the growth of Megalobrama amblycephala.